2016
DOI: 10.1209/0295-5075/113/54001
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the jamming transition of bidisperse mixtures

Abstract: Structure of disordered solids PACS 64.60.an -Phase transitions in finite-size systemsAbstract -We systematically map out the jamming transition of all 2D bidisperse mixtures of frictionless disks in the hard particle limit. The critical volume fraction, mean coordination number, number of rattlers, structural order parameters, and bulk modulus each show a rich variation with mixture composition and particle size ratio, and can therefore be tuned by choosing certain mixtures. We identify two local minima in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 32 publications
(82 reference statements)
5
44
0
Order By: Relevance
“…This comparison is particularly relevant for the large size ratios in Figs. 9(b) and 9(c) since they are close to or above the critical size ratio identified by Koeze et al [28] of * ≈ 6.46.…”
Section: F Interpolation Modelsupporting
confidence: 77%
See 2 more Smart Citations
“…This comparison is particularly relevant for the large size ratios in Figs. 9(b) and 9(c) since they are close to or above the critical size ratio identified by Koeze et al [28] of * ≈ 6.46.…”
Section: F Interpolation Modelsupporting
confidence: 77%
“…A recent study of bidisperse mixtures [28] found that the inclusion of "rattlers" (i.e., small particles with a large size ratio between large and small particles) fills in the voids between large particles and dramatically increases the critical packing fraction. However, it is unclear how the rattlers affect the dynamical response of the granular material to impact, for example, or how they affect the interstitial forces between grains.…”
Section: Effect Of Packing Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain our focus of the disordered solid regime, we work with bidisperse mixtures of cells with different preferred geometric quantities. Inspired by disk packings that frustrate the hexagonal lattice [36], we choose a 50 : 50 mixture of N = 1024 cells with a 0,α /a 0,β = 4/3 for cell types α and β. We then scale the preferred perimeters of the cells so that the dimensionless target shape parameter q 0 ≡ p 0,i / √ a 0,i is identical for all cells.…”
Section: Voronoi Modelmentioning
confidence: 99%
“…Model system.-We study mixtures of N soft disks in D ¼ 2 dimensions with equal numbers of large and small disks having a 1.4∶1 ratio of their radii, a commonly studied model system [7,34]. Unless noted otherwise, N ¼ 65 536 prior to removing nonload bearing "rattlers".…”
mentioning
confidence: 99%